Legal Politics of the Establishment of the Daya Anagata Nusantara Investment Management Agency (BPI Danantara) in Indonesia - Erwin, Yanuar Putra; Gunadi, Ariawan; Aprilia, Indah Siti; Matheus, Juan (APPS Publications, 2024)
This study examines several problems that arise in the establishment of BPI Danantara, such as the urgency of establishing BPI Danantara, the objectives of Danantara's legal policy, and the the strengths and weaknesses of establishing BPI Danantara. The writing method used in this writing is normative legal analysis. The study finds that the establishment of BPI Danantara is urgently needed to accelerate economic growth, eradicate extreme poverty, and fund downstream programs, yet its success hinges on upholding good governance, transparency, professional management, and the development of clear implementing regulations for investment management. The novelty lies in the proposed establishment of BPI Danantara as a strategic entity to address critical national economic goals, specifically through direct capital injection into downstream programs, a function previously reliant on foreign investment.